Penggunaan PMRI Berbantu Media Jaring-jaring Karakter - Dwi Aprilia, Nesa; Zuliana, Eka (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the use of the PMRI (Indonesian Realistic Mathematics Education) approach with the help of character net media in mathematics learning. PMRI is known as an approach that connects mathematics learning with real world contexts to improve students' understanding and abilities. Character web media is used to help students understand mathematical concepts visually and concretely, as well as to increase interaction and collaboration between students. This research was carried out at SDN Karangbener 2. The sample in this research was class 2, consisting of 10 students, namely 5 boys and 5 girls. This research is a type of qualitative research using research methods, namely descriptive qualitative. The data collection techniques used were documentation, interviews and observation. The data analysis process was carried out qualitatively interactively. The results of the research show that the use of PMRI assisted by character net media can increase students' understanding of spatial building material, especially cube and block building.